Development of Nested PCR and Duplex Real-Time Fluorescence Quantitative PCR Assay for the Simultaneous Detection of Theileria equi and Babesia caballi - Lv, Kunying; Zhang, Yiwei; Yang, Yixin; Liu, Zheng; Deng, Liang (Frontiers in Veterinary Science, 2022)
Equine piroplasmosis (EP) is a type of blood protozoan disease caused by tick-borne parasites, Theileria equi (T. equi), Babesia caballi (B. caballi) and Theileria haneyi. While many studies have been conducted on EP diagnosis, diagnostic methods exhibiting high sensitivity and specificity remain lacking. Therefore, nested PCR (nPCR) and duplex real-time fluorescence quantitative PCR (qPCR) that can simultaneously detect both T. equi and B. caballi causing agents were established and compared. The two techniques were used to analyze 36 horse blood samples for EP. This set of samples was also detected by a multinested PCR (mnPCR) targeting the EMA-1 gene of T. equi and the RAP-1 gene of B. caballi. By nPCR, duplex real-time fluorescence qPCR and mnPCR, infections with B. caballi were detected in 16.67% (6/36), 2.78% (1/36), 19.44% (7/36) of the horses, respectively. The T. equi prevalence was 58.33% (21/36) by the nPCR, 33.33% (12/36) by the duplex real-time fluorescence qPCR and 2.78% (1/36) by the mnPCR. The overall prevalence of infection with mixed parasites by nPCR was 5.56% (2/36), by duplex real-time fluorescence qPCR was 2.78% (1/36) and by mnPCR 0% (0/36). Results suggest that nPCR can detect T. equi and B. caballi positive samples with good specificity and sensitivity, although distinguishing between the two parasites requires an electrophoresis with 4% agarose gels. The duplex real-time fluorescence qPCR can readily distinguish between T. equi and B. caballi infection, but with low sensitivity.